(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This research paper explores the intricate functionalities and best practices of working with images and backgrounds in WordPress, one of the most popular content management systems (CMS). As visual content becomes increasingly vital in web design, understanding how to effectively use images and backgrounds is crucial for creating engaging and aesthetically pleasing websites. This paper covers the technical aspects of image manipulation, optimization techniques, and background customization in WordPress. Additionally, it delves into the use of plugins and themes to enhance image-related functionalities, ensuring that web pages not only look professional but also perform efficiently.